Why resilient workers perform better: The roles of job satisfaction and work engagement. (2nd January 2018) - Kašpárková, Ludmila; Vaculík, Martin; Procházka, Jakub; Schaufeli, Wilmar B.
ABSTRACT: Previous studies have confirmed correlations between resilience and job performance, but surprisingly little is known about the nature of this relationship. This study sheds light on the roles of two important positive dimensions of work-related well-being: job satisfaction and work engagement. Data were collected from 360 Czech workers in helping professions using an online survey. Levels of resilience and perceived job performance were indeed positively associated. Using structural equation modeling, the best-fitting model showed partial mediation by work engagement; conversely, job satisfaction was not found to be a mediator of this relationship. Additionally, the finding that job performance is related more strongly to work engagement than to job satisfaction contributes to the debate about the concurrent validity of job attitudes.